SHOT ANALYSIS OF ELITE WOMEN HANDBALL PLAYERS DURING ORGANISED OFFENSE ATTEMPTS - Athanasios YIANNAKOS (Cluj University Press, 2016)
During the last years and as a result of the recently adopted rules, handball has evolved to a very fast game, with goal-attempts transposing to an important factor influencing the final result of the game. The aim of the present study was to evaluate the performed shots according to a) the total number of attack attempts, b) the adopted offensive formation, c) the positioning of the thrower, d) the final positioning of the ball within the goalpost and e) their efficacy among elite women handball players. All matches of the eight finalists women's National Teams competing at the 2008 Olympic Games, were recorded. The total number of attacks (n=3,264) was evaluated with video-analysis software. Non-parametric Chi-square tests were used to assess differences (p